Connecting Theory to Practice: Mathematics, Physics, and Mobile Robotics in Our Daily Lives - Araujo Neto, Wolmar; Rezende, João Pedro Da Silva; Pimenta, Maurício Bittencourt; Bacheti, Vinícius Pacheco; Sarcinelli-Filho, Mário; Villa, Daniel Khede Dourado (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2024: Anais do XVI Simpósio Brasileiro de Robótica e XV Workshop de Robótica na Educação, 2024)
This article presents an outreach project focused on developing educational videos to teach mathematical and physical fundamentals applied to robotics and intelligent automation. Initially, the videos demonstrate the practical application of these concepts in the Laboratory of Autonomous Intelligent Robots (LAB-AIR), with plans to expand the content to include tutorials and undergraduate topics. The videos will be made available on platforms such as YouTube, TikTok, Instagram, and LinkedIn to democratize knowledge and engage new students and researchers with the Federal University of Espírito Santo and LAB-AIR. The project stands out for aligning research in robotics and automation with the university's mission of promoting knowledge and fostering scientific dissemination and education.